Effective Scholarship Strategies: A Motivational Workshop for Undergraduate Students of Islamic Higher Education Institutions - Rahman, Fadhlur; Armanda, Dicky; Jailani, Munawar Rizki; Hasanah, Uswatun (Pengabdian Cendekia, 2024)
One concrete embodiment of community service is the giving of assistance to students who are struggling with academic challenges, such as scholarships. The session was constructed with a participatory and practical design, with the purpose of ensuring that participants not only grasped the theoretical content but could also apply it immediately. On the first day, the workshop session showcased authentic CVs that captivated the interest of scholarship prospective candidates. Participants endeavoured to organize their CVs with the assistance of the speakers. The second day was filled with writing motivational letters and preparing for interviews. In addition, role-playing exercises resembled scheduled interviews. Participants alternated between roles as interviewers and candidates. This practice was intended to improve their confidence and communication abilities. The program was successful in meeting its goal of equipping students with the knowledge and abilities needed to submit scholarship applications. Participants in this exercise not only improved their technical understanding, but also gained confidence in their ability to compete for scholarship opportunities.